2017
DOI: 10.3390/coatings7120236
|View full text |Cite
|
Sign up to set email alerts
|

Photonic Structures for Light Trapping in Thin Film Silicon Solar Cells: Design and Experiment

Abstract: Abstract:One of the foremost challenges in designing thin-film silicon solar cells (TFSC) is devising efficient light-trapping schemes due to the short optical path length imposed by the thin absorber thickness. The strategy relies on a combination of a high-performance back reflector and an optimized texture surface, which are commonly used to reflect and scatter light effectively within the absorption layer, respectively. In this paper, highly promising light-trapping structures based on a photonic crystal (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Ding et al [ 28 ] investigated a nanocone grating with architecture with a high aspect ratio and a dense periodicity of about 500 nm. This configuration was applied at the front surface as an antireflection coating, and it was successfully demonstrated that a substantial increase in absorption could be obtained.…”
Section: Nanoparticle Material Size and Shape Effectsmentioning
confidence: 99%
See 3 more Smart Citations
“…Ding et al [ 28 ] investigated a nanocone grating with architecture with a high aspect ratio and a dense periodicity of about 500 nm. This configuration was applied at the front surface as an antireflection coating, and it was successfully demonstrated that a substantial increase in absorption could be obtained.…”
Section: Nanoparticle Material Size and Shape Effectsmentioning
confidence: 99%
“…( B ) SEM images of MCPS (P3H0.5, P3H1.0, P3H1.5), MCPS coated with Ag/AZO, and a corresponding solar cell. ( C ) SEM images of microcone structure (MCS), quasicrystal structure (QCS), and MCS-based and QCS-based a-SiGe:H solar cells [ 28 ] (reprinted with permission from [ 28 ], 2017, Creative Commons CC-BY license).…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Its collection, conversion, and storage still require significant technological improvements in order to fully realize its potential as a fossil fuel replacement [1]. The current photovoltaic (PV) market is thus still dominated by first-generation crystalline silicon solar cells (~95% share), which can achieve a maximum PV conversion efficiency of ~26%, despite their high production and implementation costs [2][3][4]. Second-generation devices based on thin-film solar cells (TFSCs) have emerged due to the necessity of lowering production costs, reducing material expenditure, and increasing mechanical flexibility, therefore enabling a much wider range of applications.…”
Section: Introductionmentioning
confidence: 99%